Perceptions of sexual violence among men who have sex with men and individuals on the trans-feminine spectrum in Mongolia. Issue 8 (3rd August 2017) - Peitzmeier, Sarah M.; Stephenson, Rob; Delegchoimbol, Altanchimeg; Dorjgotov, Myagmardorj; Baral, Stefan
ABSTRACT: With the growing realisation that sexual violence poses pressing health and human rights concerns for men who have sex with men (MSM) and individuals on the trans-feminine spectrum, research has focused on the context in which sexual violence takes place. Rape myths and other perceptions of sexual violence affect the prevalence of perpetration and the availability of services and support for survivors. Little research has been conducted on rape myths among sexual and gender minority groups, especially in low- and middle-income countries. Two focus groups and 30 in-depth interviews were conducted with MSM and individuals on the trans-feminine spectrum in Ulaanbaatar, Mongolia. A number of rape myths previously noted to be prevalent among Western, heterosexual men, and women were expressed by participants, including the myth that males are never raped, rape as a cause of homosexuality or transgenderism, conceptualisations of prototypical rape as requiring overwhelming force, and victim blaming. However, many of these perceptions appeared to have different origins and effects in these populations. This study illustrates interesting similarities and differences compared to rape myths explored in Western, heterosexual male samples, and draws attention to the need to address community perceptions of sexual violence in sexual health and violence intervention programming.